Permanganate oxidizable carbon for soil health: Does drying temperature matter?. Issue 1 (10th June 2020) - Gasch, Caley; Mathews, Shiny; Deschene, Alec; Butcher, Kirsten; DeSutter, Thomas
Abstract: Soil health assessments evaluate and monitor the effects of conservation management on soil properties. A popular measurement, permanganate oxidizable carbon (POXC), is routinely included in these assessments. The standard POXC protocol calls for air‐dried soil samples, but commercial laboratories typically dry samples in a forced‐air oven before routine analysis. In order to evaluate if heat would change POXC measurements, we treated soil (52 silty clay loam and 51 sandy loam samples) with oven drying at 45 and 65 °C and compared their POXC values with those from air‐dried samples. We also examined relationships between POXC values and soil organic matter, pH, and electrical conductivity across drying treatments. Drying soil did not substantially change POXC values for either soil texture and did not change the relationships between POXC and other measured soil properties. This work suggests that commercial laboratories could perform POXC analysis on soil samples dried using heat.